PSYCHOLOGICAL MODEL OF ADOLESCENT COMMUNICATION AFTER GRIEF - Dortje L. Y. Lopulalan; Yulian Hermanus Wenno (Adisam Publisher, 2024)
The death of parents is a very sad event for adolescents because then the family is no longer intact, there will be many changes and adjustments that occur. This also does not rule out the possibility of causing conflict in adolescents due to the grief crisis. This study aims to construct a model of communication psychology that is relevant for adolescents after grief by using an explanatory qualitative research method with a phenomenological approach. This approach seeks to describe the meaning of individual life experiences of adolescents according to their own worldview because in the act of reinteraction individuals are active in interpreting and displaying social behavior subjectively. The findings explain that adolescents feel psychologically comfortable through social support from people around them, namely family and peers, because there are shared experiences, emotional reinforcement is felt so that they feel loved, cared for, valued and even a teenager feels mutual need and belonging in any condition through intense interpersonal communication.